TI verde ??? o armazenamento de dados e a efici??ncia energ??tica no data center de um banco brasileiro - Silva, Newton Rocha da (2015)
The Green IT focuses on the study and design practice, manufacturing, use and disposal of computers, servers, and associated subsystems, efficiently and effectively, with less impact to the environment. It??s major goal is to improve performance computing and reduce energy consumption and carbon footprint. Thus, the green information technology is the practice of environmentally sustainable computing and aims to minimize the negative impact of IT operations to the environment. On the other hand, the exponential growth of digital data is a reality for most companies, making them increasingly dependent on IT to provide sufficient and real-time information to support the business. This growth trend causes changes in the infrastructure of data centers giving focus on the capacity of the facilities issues due to energy, space and cooling for IT activities demands. In this scenario, this research aims to analyze whether the main data storage solutions such as consolidation, virtualization, deduplication and compression, together with the solid state technologies SSD or Flash Systems are able to contribute to an efficient use of energy in the main data center organization. The theme was treated using qualitative and exploratory research method, based on the case study, empirical and documentary research such as technique to data collect, and interviews with IT key suppliers solutions. The case study occurred in the main Data Center of a large Brazilian bank. As a result, we found that energy efficiency is sensitized by technological solutions presented. Environmental concern was evident and showed a shared way between partners and organization studied. The maintaining of PUE - Power Usage Effectiveness, as energy efficiency metric, at a level of excellence reflects the combined implementation of solutions, technologies and best practices. We conclude that, in addition to reducing the consumption of energy, solutions and data storage technologies promote efficiency improvements in the Data Center, enabling more power density for the new equipment installation. Therefore, facing the digital data demand growth is crucial that the choice of solutions, technologies and strategies must be appropriate not only by the criticality of information, but by the efficient use of resources, contributing to a better understanding of IT importance and its consequences for the environment.